2012
DOI: 10.1371/journal.pone.0030508
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Histone Deacetylase Activity in Human Endometrial Stromal Cells Promotes Extracellular Matrix Remodelling and Limits Embryo Invasion

Abstract: Invasion of the trophoblast into the maternal decidua is regulated by both the trophoectoderm and the endometrial stroma, and entails the action of tissue remodeling enzymes. Trophoblast invasion requires the action of metalloproteinases (MMPs) to degrade extracellular matrix (ECM) proteins and in turn, decidual cells express tissue inhibitors of MMPs (TIMPs). The balance between these promoting and restraining factors is a key event for the successful outcome of pregnancy. Gene expression is post-transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…In four-week-old guinea pigs, it was demonstrated that the retinal levels of the TGF-β2 protein are highly correlated with ocular refraction and axial length (22). TGF-β2 is a key factor in the progression of myopia development and axial elongation; however, reports of its expression in experimental myopia have been controversial as animal studies have demonstrated increases and decreases (22)(23)(24)(25)(26). It appears that the changes in TGF-β2 expression during the development of myopia are species-and tissue-specific (22-24,25,27).…”
Section: Discussionmentioning
confidence: 99%
“…In four-week-old guinea pigs, it was demonstrated that the retinal levels of the TGF-β2 protein are highly correlated with ocular refraction and axial length (22). TGF-β2 is a key factor in the progression of myopia development and axial elongation; however, reports of its expression in experimental myopia have been controversial as animal studies have demonstrated increases and decreases (22)(23)(24)(25)(26). It appears that the changes in TGF-β2 expression during the development of myopia are species-and tissue-specific (22-24,25,27).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the uterine epithelium undergoes remodelling at the site of the implanting embryo/blastocyst (Schlafke et al 1985, Welsh & Enders 1991, Ramathal et al 2011, Estella et al 2012. The proliferating stromal cells differentiate to form the uterine interface with the placenta, which is referred to as the decidua (Bell 1983), and decidualisation is essential for successful reproduction (Lydon et al 1995, Robb et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…Even simpler models using decidualizing endometrial stromal cells in co-culture with trophoblast cells or trophoblast-cell-conditioned medium have also been reported Hess et al, 2007). Studies employing a co-culture model with mouse embryos and decidualizing human endometrial stromal cells to study embryo-endometrium interactions revealed the importance of endometrial stromal cell integrins in blastocyst development (outgrowth) and differentiation following attachment (Shiokawa et al, 1996) and showed that endometrial stromal cell histone deacetylase may promote trophoblast spreading of a day-4 hatched mouse embryo (as well as endometrial stromal cell migration and Jeg-3 trophoblast invasion) (Estella et al, 2012). In another heterologous in-vitro co-culture model, it was shown that inhibition of endometrial stromal cell motility suppressed mouse blastocyst invasion into the monolayer (Grewal et al, 2008).…”
Section: Using Embryo Surrogatesmentioning
confidence: 99%